Frequency of causative agents of urinary tract infections in patients from the territory of the City of Prokuplje - Bogdanović, Svetlana; Zlatković, Ivana; Zlatanovic, Zvonko; Randjelovic, Dobrila; Vacic, Nebojsa (PONS - medicinski časopis, 2023)
Every year, around 150 million people worldwide are diagnosed with some type of urinary tract infection. Urinary tract infections are the second most common, after respiratory infections. The aim of this paper is the microbiological analysis of the urine of primary health care patients on the territory of the municipality of Prokuplje. The six-month urinalysis included a total of 706 samples. Of the tested samples, 388 (54.96%) were positive for pathogenic microorganisms. The most common pathogen is E. coli with a share of 67.52% in relation to the number of positively tested samples. Then follow Proteus spp. with 10.57%, Enterococcus spp. with 9.54%, Enterobacter spp. with 5.67%, Klebsiella spp. with 2.58%, Psedomonas aeruginosa with 1.55%, S. aureus with 1.03% and C. albicans and Gardnerella vaginalis with 0.77% each in relation to the number of positively tested samples. According to the gender distribution of Gram-negative bacteria, the most common among women is Proteus spp. (82.93%), while in men the most common Klebsiella spp. (80%). Of the Gram-positive bacteria, S. aureus and Gardnerella vaginalis are 100% present only in the female population, as is C. albicans. When choosing antibiotic therapy for patients with urinary infections, it is very important to harmonize the therapy with the age and gender of the patient.